Chemical Constituents and Cytotoxic Activity of Lobelia alsinoides Lam – A Wild Food Resource - Samdavid Thanapaul, Rex Jeya Rajkumar; Giriraj, Kalaiarasi; Paulraj, Mosae Selvakumar; Nadar, MSA Muthukumar (Chemistry Africa, 2024)
The Lobelia alsinoides Lam plant has traditionally been consumed as a wild food supplement by rural communities in Thailand’s north-eastern Kalasin province. Despite its traditional use, there has been a lack of scientific research to validate Lobelia alsinoides Lam’s biological properties. This is the first study to identify and characterize the ethanolic extract of Lobelia alsinoides Lam and assess it’s in vitro cytotoxic potential. Various spectroscopic techniques, including infrared (IR) spectroscopy, NMR spectroscopy ( 1 H and 13 C), and mass spectroscopy (LC-QTOF-MS), were used to characterize the Lobelia alsinoides Lam ethanolic extract. The extract was then tested for cytotoxicity against various cancerous cell lines (A549, KB, HeLa, MDA-MB-231, and MCF-7). Spectral investigation on the ethanolic extracts of the Lobelia alsinoides Lam’s plant afforded four components namely 5-{2-[(3,4-Dihydroxy-5-methyl-phenyl)-methyl-amino]-propoxy}-4,6-dimethyl-tetrahydro-pyran-2,3-diol ( 1 ), (3,4-Dimethyl-phenyl)-methyl-carbamic acid 3,4,5-trihydroxy-6-methyl-tetrahydropyran-2-yl ester ( 2 ); 5-{[3-(2,6-Dimethyl-tetrahydro-pyran-3-yl)-1-methyl-propyl]-methyl-amino}-benzene-1,2,3,4-tetraol ( 3 ); 3-Hydroxy-5-[3,4,5-trihydroxy-6-(3,4,5-trihydroxy-6-methyl-tetrahydro-pyran-2-yloxymethyl)-tetrahydro-pyran-2-yloxy]-pent-3-enoic acid methyl-(2,3,4,5-tetrahydroxy-phenyl)-amide ( 4 ). The ethanol extract of Lobelia alsinoides Lam was found to have a significant cytotoxic effect in a dose-dependent manner against five human cancer cells. The LDH release assay and the NO inhibitory assay confirmed Lobelia alsinoides Lam’s anti-proliferative and anti-inflammatory effects in vitro compared with the standard drug cisplatin. According to our findings, the wild food source Lobelia alsinoides Lam is non-toxic and may have cytotoxic activity against human cancers such as lung, breast, cervical, and oral. Graphical Abstract Highlights First study to report the characterization of ethanolic extract of Lobelia alsinoides Lam using FTIR, NMR ( 1 H and 13 C), and mass spectroscopy (LCMS-QTOF-MS). L. alsinoides Lam ethanol extract was found to have a potent cytotoxic effect in dose-dependent response against the five human cancer cells (A549, KB, HeLa, MDA-MB-231, and MCF-7) LDH release assay, and the NO inhibitory assay, confirmed the in vitro antiproliferative and anti-inflammatory effects of L. alsinoides Lam